Copolymer, anti-rust coating composition containing same, dispersant and resist resin
A copolymer with adjacent phenolic hydroxyl groups and a dispersant with specific monomers address adhesion and stability issues in metal coatings, ensuring effective rust prevention and stable dispersion of fine particles under harsh conditions.
Patent Information
- Application Number
- JP2021574046
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-31
- Filing Date
- 2021-01-26
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2041-01-26
AI Technical Summary
Existing polymers used for rust prevention and dispersants in metal coatings fail to provide adequate adhesion and stability under harsh environmental conditions, leading to corrosion and dispersion instability, particularly with fine particles, affecting the quality and productivity of coated materials.
A copolymer containing adjacent phenolic hydroxyl groups forms chelate structures with metal surfaces, enhancing adhesion and rust prevention, while a dispersant with specific monomer compositions ensures high concentration dispersion stability and initial dispersibility of fine particles.
The copolymer provides excellent rust prevention and adhesion under harsh conditions, and the dispersant maintains stable dispersion of fine particles, improving the durability and quality of coated materials.
Smart Images

Figure 0007618131000001 
Figure 0007618131000002 
Figure 0007618131000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a copolymer, an anticorrosive coating composition, a dispersant and a resist resin containing the copolymer. [Background technology]
[0002] Metals such as steel, whose main component is iron, magnesium, aluminum, and titanium, and alloys that contain these as their main components, are widely used as structural materials in many fields, such as marine structures, port facilities, ships, architecture, civil engineering structures, and automobiles, but they suffer from the problem of corrosion when exposed to the natural environment. Structural materials are required to have high durability, and depending on the usage environment, they need to be able to withstand harsh environments such as exposure to seawater, so various rust prevention treatment methods are used to prevent corrosion.
[0003] Chromate treatment and chromate phosphate treatment, which use highly toxic chromium compounds, are commonly used as anti-rust treatment methods, but there is a risk that they will be restricted in the future due to their toxicity.As an alternative method, a method has been proposed in which the metal surface is coated with a polymer to prevent contact with oxygen, moisture, and salt, which cause corrosion.
[0004] Examples of monomers that are effective in improving adhesion include monomers having a hydroxy group, such as hydroxyethyl (meth)acrylate and glycerin mono(meth)acrylate, and monomers having a carboxy group, such as acrylic acid and methacrylic acid. Patent Document 1 discloses the addition of glycerin monomethacrylate as an adhesion improving component.
[0005] Furthermore, Patent Document 2 discloses a dental adhesive in which a hardening composition containing a gallic acid or tannic acid derivative and a pyrophosphate ester of methacrylic acid or the like has excellent adhesion to dentin and antibacterial effect.
[0006] Dispersion compositions in which organic or inorganic powders are dispersed in a solvent are used in various industrial fields. Examples of organic powders include organic pigments, and dispersion compositions containing organic pigments are used in paints, inks, color resists, and the like. Examples of inorganic powders include ceramic powders and metal powders, and dispersion compositions containing ceramic powders are used in abrasives, fireproof materials, and the like, as well as in electronic components such as dielectric layers of laminated ceramic capacitors, semiconductor substrates, and various sensors. Dispersion compositions containing metal powders are widely used, for example, as conductive pastes or conductive inks for the electrode layers of laminated ceramic capacitors and circuit-forming materials for substrates.
[0007] In recent years, there has been a demand for electronic component applications to improve product characteristics, such as miniaturization and high performance. For example, in order to make multilayer ceramic capacitors smaller and more highly-capacitive, the barium titanate in the dielectric layer is becoming finer. In color resists, the organic pigments are becoming more concentrated to improve the color reproducibility of liquid crystal displays. Thus, there is a demand for finer particles of various powders and higher concentrations of dispersions in dispersion compositions.
[0008] When preparing a dispersion composition, since the dispersibility of the powder alone is often insufficient, a dispersant is generally used to improve the fluidity and storage stability of the dispersion composition. However, with the microparticulation, in conventional polymeric dispersants, the dispersant is likely to cause bridging aggregation in which the dispersant is adsorbed across particles, resulting in a decrease in initial dispersibility. In addition, since the surface area of the dispersion increases, the surface free energy of the dispersion increases, and the dispersion system is likely to become unstable. Even if the dispersion is once dispersed, the dispersion will aggregate again in an attempt to reduce the apparent surface area of the dispersion, making it difficult to maintain the dispersion state stably. The decrease in initial dispersibility and dispersion stability associated with the microparticulation of the dispersion causes problems such as thickening of the dispersion composition and sedimentation of the dispersion. A dispersion composition with these problems not only leads to a decrease in productivity, processing characteristics, and handling properties, but also leads to a decrease in the quality of the final product.
[0009] For this reason, the dispersant is required to have the ability to obtain a dispersion composition that contains a high concentration of the dispersant and has a low viscosity, and to stably disperse the dispersant for a long period of time without causing sedimentation.
[0010] In order to solve these problems, polymeric dispersants such as polyacrylic acid and copolymers thereof, and copolymers of polyoxyalkylene derivatives and maleic anhydride have been proposed as dispersants, as shown in Patent Document 3.
[0011] Photoresist materials are widely used and have become indispensable fine processing materials in the manufacturing or processing of electronic components, including image display devices such as televisions and image pickup devices used in digital cameras.
[0012] Image display devices and imaging devices have insulating films, color filters, and spacers, which are formed from photoresist materials. With the recent trend toward smaller and finer electronic products, there is a strong demand for improved resist performance. For example, in pigment-dispersed resist compositions used to form color filters, reductions in the resin components in the composition and increases in the pigment concentration have been considered, but these tend to cause a decrease in sensitivity and a decrease in adhesion to the substrate, and therefore there is a demand for improved adhesion to the resist composition. Furthermore, with the increase in in-vehicle electronic devices and increased overseas transportation, there is a growing demand for adhesion in high temperature and high humidity environments.
[0013] As a method for improving adhesion, Patent Document 4 discloses a method of adding a silane coupling agent such as epoxy, (meth)acrylic, or vinyl to a photosensitive resin composition. Furthermore, as a method for improving adhesion at room temperature and also at high temperature and humidity, Patent Document 5 discloses a method of adding an organosilicon compound having a (meth)acrylic or urethane structure. [Prior art documents] [Patent documents]
[0014] [Patent Document 1] JP 2014-118508 A [Patent Document 2] Japanese Patent Application Publication No. 7-138119 [Patent Document 3] Patent Publication No. 2016-222852 [Patent Document 4] Japanese Patent Application Publication No. 10-133370 [Patent Document 5] JP 2018-159930 A Summary of the Invention [Problem to be solved by the invention]
[0015] Polymers composed of monomers such as those described in Patent Document 1 have a high adsorption power to metal surfaces, and therefore exhibit excellent adhesion and provide a certain level of rust prevention effect. However, when exposed to harsh environments such as the seashore, it is not possible to completely prevent moisture from coming into contact with the metal surface, and the rust prevention effect is insufficient.
[0016] Furthermore, polymers composed of monomers such as those described in Patent Document 2 require curing by ultraviolet light or heat, and as a coating material, they do not provide sufficient adhesion to metal substrates or sufficient anti-rust effect. As described above, there is a demand for coating materials that exhibit excellent rust prevention effects even under severe conditions.
[0017] However, the dispersant described in Patent Document 3 was not sufficient in terms of obtaining a dispersion composition containing a high concentration of dispersing matter and having a low viscosity, and in terms of stably dispersing the dispersing matter for a long period of time without causing sedimentation.
[0018] Furthermore, when ceramic dielectric layers and metal electrode layers are laminated and fired, as in the case of multilayer ceramic capacitors, the electrode layers and dielectric layers have different shrinkage rates during firing, which can cause defects such as interface peeling, so a method is used in which the same ceramic particles as the dielectric layer, called a co-material, are added to the metal paste. In this case, a method is being considered in which a dispersant for ceramic particles is mixed when preparing the metal paste containing the co-material, but this causes problems such as a decrease in the stability of the metal paste and a decrease in compatibility between dispersants and with other additives such as binder resins, limiting the dispersants that can be used. For this reason, there has been a demand for a dispersant that has high dispersibility and dispersion stability for metal fine particles and ceramic fine particles even when used alone.
[0019] In addition, in the compositions described in Patent Documents 4 and 5, the addition of each component is intended to improve adhesion, but there is a concern that the incorporation of the additives may decrease the stability of the composition over time, etc. In addition, in Patent Documents 4 and 5, a known compound is used for the resist resin, which is the main component of the resist resin composition, and the properties of the resist resin are not improved.
[0020] An object of the present invention is to provide a novel copolymer that can provide a coating material having excellent rust prevention effect. Another object of the present invention is to provide a coating material having excellent rust prevention effect.
[0021] An object of the present invention is to provide a dispersant capable of dispersing a fine particle dispersion in a solvent at a high concentration and imparting excellent dispersion stability.
[0022] Another object of the present invention is to provide a resist resin which can provide a pattern with good adhesion both at room temperature and under high-temperature and high-humidity conditions. [Means for solving the problem]
[0023] As a result of investigations aimed at solving the above-mentioned problems, the present inventors focused on a structure containing adjacent phenolic hydroxyl groups in a polymer, and discovered that the adjacent phenolic hydroxyl groups form a chelate structure with the metal surface, thereby establishing a strong coordinate bond, thereby exhibiting excellent adhesion and excellent rust prevention effect even under harsh conditions, thereby solving the above-mentioned problems.
[0024] Furthermore, as a result of investigations aimed at solving the above-mentioned problems, the present inventors focused on a structure containing adjacent phenolic hydroxyl groups in a polymer, and discovered that adjacent phenolic hydroxyl groups exert strong adsorption power on the powder surface by forming a chelate structure or by π-π interactions with aromatic rings, thereby showing excellent initial dispersibility and dispersion stability even for fine particles, thereby solving the above-mentioned problems. Furthermore, as a result of investigations aimed at solving the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by a resist resin comprising a monomer having a specific structure, the monomer having adjacent phenolic hydroxyl groups in the polymer.
[0025] That is, the present invention is as follows. (1) A copolymer, comprising: a monomer (A) represented by the following general formula (1) in a molar ratio of 1 to 99 mol %, a (meth)acrylic acid alkyl ester (B) having 1 to 22 carbon atoms in a molar ratio of 1 to 99 mol %, another copolymerizable monomer (C) in a molar ratio of 0 to 98 mol %, and a weight average molecular weight of 3,000 to 1,000,000. [ka] (In formula (1), R is a hydrogen atom or a methyl group, X represents an alkylene group having 2 to 5 carbon atoms or an alkylene group having 2 to 5 carbon atoms and one hydroxyl group.
[0026] (2) An anticorrosive coating composition comprising the copolymer of (1) and an organic solvent.
[0027] (3) A dispersant comprising the copolymer of (1).
[0028] The dispersant according to (3), characterized in that the copolymer is a copolymer containing a constituent component derived from the monomer (C), and the monomer (C) is a (meth)acrylic acid polyoxyalkylene ester represented by the following general formula (2): [ka] (In formula (2), R 1 is a hydrogen atom or a methyl group, R 2 is a hydrogen atom or an alkyl group having 1 to 22 carbon atoms, OA is an oxyalkylene group having 2 to 4 carbon atoms; n is the average number of moles of the oxyalkylene group added and is 1 to 50.
[0029] (5) A dispersion composition comprising the dispersant of (3) or (4), a solvent, and a dispersion dispersed by the dispersant.
[0030] (6) A resist resin comprising the copolymer of (1), a molar ratio of the monomer (A) is 1 to 40 mol %, a molar ratio of the (meth)acrylic acid alkyl ester (B) is 1 to 94 mol %, the other monomers (C) contain at least a monomer (C1) having a carboxyl group, a molar ratio of the monomer (C1) having a carboxyl group is 5 to 40 mol %, a molar ratio of a copolymerizable monomer (C2) other than the monomer (C1) having a carboxyl group is 0 to 93 mol %, and a weight average molecular weight is 3,000 to 100,000. Effect of the Invention
[0031] The copolymer of the present invention is a novel copolymer containing a monomer having a specific structure containing adjacent phenolic hydroxyl groups. Since the adjacent phenolic hydroxyl groups are strongly coordinated to the metal surface, the anti-rust coating composition containing the copolymer can impart an excellent anti-rust effect to the metal. As a result, the metal material using the anti-rust coating composition of the present invention has excellent durability due to the high anti-rust effect.
[0032] According to the invention of the dispersion composition of the present invention, it is possible to disperse fine particle dispersions such as organic or inorganic powders having a particle diameter of 1 μm or less in a solvent at a high concentration and to impart excellent dispersion stability.
[0033] According to the resist resin of the present invention, a resin film having good adhesion can be obtained both at room temperature and under high temperature and high humidity conditions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0034] Hereinafter, an embodiment of the present invention will be described. [Monomer (A)] The monomer (A) used in the present invention is represented by the following general formula (1). [ka]
[0035] In formula (1), R is a hydrogen atom or a methyl group, and from the viewpoints of the stability of the monomer and ease of polymerization, a methyl group is particularly preferred. X represents an alkylene group having 2 to 5 carbon atoms or an alkylene group having 2 to 5 carbon atoms and one hydroxyl group. The alkylene group having one hydroxyl group has a carbon chain of the alkylene group and one hydroxyl group on the carbon chain. From the viewpoint of hydrophilicity and ease of synthesis, X is preferably an alkylene group having one hydroxyl group, and more preferably X has 2 to 4 carbon atoms, and particularly preferably X has 3 carbon atoms. The substitution position of the hydroxyl group on the alkylene group is preferably the 2-position or 3-position, and more preferably the 2-position. Specific examples of X include an ethylene group, a propylene group, a butylene group, a pentylene group, a 1-hydroxyethylene group, a 2-hydroxypropylene group, a 2-hydroxybutylene group, a 3-hydroxybutylene group, a 2-hydroxypentylene group, and a 3-hydroxypentylene group. The substitution position on the benzene ring of XOC(O)- is the 4- or 5-position on the benzene ring, but from the viewpoint of raw material availability, a structure derived from gallic acid at the 5-position is particularly preferred. The monomer (A) may be used alone or in combination of two or more kinds.
[0036] When the total monomers constituting the copolymer are taken as 100 mol%, the molar ratio of monomer (A) is 1 mol% or more. If the molar ratio of monomer (A) is too low, there is a risk of reduced adhesion, so the molar ratio is 5 mol% or more, preferably 7 mol% or more, and more preferably 10 mol% or more.
[0037] When all the monomers constituting the copolymer are taken as 100 mol %, the molar ratio of the monomer (A) is 99 mol % or less. From the viewpoint of ease of polymerization, the molar ratio of the monomer (A) is preferably 50 mol % or less, more preferably 40 mol % or less, and particularly preferably 30 mol % or less.
[0038] (Monomer (B)) The monomer (B) used in the present invention is a (meth)acrylic acid alkyl ester having 1 to 22 carbon atoms. The alkyl chain length of the (meth)acrylic acid alkyl ester is from 1 to 22 carbon atoms, and from the viewpoints of dispersibility and solubility in various solvents, the alkyl chain length is preferably from 2 to 22 carbon atoms, and more preferably from 4 to 18 carbon atoms. For example, examples of the (meth)acrylic acid ester monomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate. Of these, linear alkyl groups such as butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, and stearyl (meth)acrylate are preferred, with butyl (meth)acrylate or stearyl (meth)acrylate being more preferred, and butyl (meth)acrylate being even more preferred.
[0039] In the case of dispersants, the alkyl chain length of the (meth)acrylic acid alkyl ester is 1 to 22 carbon atoms, and from the viewpoint of adhesiveness and glass transition point of the copolymer, the alkyl chain length is preferably 1 to 12 carbon atoms, and more preferably 2 to 10 carbon atoms. Examples of the (meth)acrylic acid ester monomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate, and ethyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and octyl (meth)acrylate are preferred.
[0040] In the case of a resist resin, the aliphatic alkyl chain of the (meth)acrylic acid alkyl ester has an alkyl chain length of 1 to 22 carbon atoms, and from the viewpoints of adhesiveness and the glass transition point of the polymer, the alkyl chain length preferably has 1 to 12 carbon atoms, more preferably has 1 to 8 carbon atoms, even more preferably has 1 to 4 carbon atoms, and particularly preferably has 1 carbon atom. Examples of the (meth)acrylic acid ester monomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate. Methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and octyl (meth)acrylate are preferred, and methyl (meth)acrylate is more preferred. The alicyclic alkyl chain of the (meth)acrylic acid alkyl ester has an alkyl chain length of 6 to 12 carbon atoms, and from the viewpoints of heat resistance and chemical resistance, the alkyl chain length is preferably 6 to 10 carbon atoms, and more preferably 6 carbon atoms. Examples of the alicyclic (meth)acrylic acid ester monomer include cyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, and dicyclopentanyl (meth)acrylate, with cyclohexyl (meth)acrylate being preferred.
[0041] The monomer (B) may be used alone or in combination of two or more kinds. When the total monomers constituting the copolymer are taken as 100 mol%, the molar ratio of monomer (B) is 1 mol% or more. If the molar ratio of monomer (B) is too low, the solubility in the solvent may decrease, so the molar ratio is 1 mol% or more, preferably 10 mol% or more, and more preferably 20 mol% or more. The molar ratio of monomer (B) is 99 mol% or less, but from the viewpoint of dispersibility, it is preferably 70 mol% or less, and more preferably 30 mol% or less. In the case of a dispersant, when the total monomers constituting the copolymer are taken as 100 mol%, the molar ratio of monomer (B) is 1 mol% or more. If the molar ratio of monomer (B) is too low, there is a risk of reduced adhesion, so the molar ratio is 1 mol% or more, preferably 50 mol% or more, and more preferably 65 mol% or more.
[0042] (Monomer (C)) The other monomer (C) copolymerizable with the monomer (A) and the monomer (B) is not particularly limited as long as it is a monomer copolymerizable with the monomer (A) and the monomer (B), and may contain one or more types. However, (meth)acrylic acid esters other than (meth)acrylic acid alkyl esters, aromatic vinyl compounds, and acrylamide compounds are preferred.
[0043] Examples of aromatic vinyl compounds include styrene, α-methylstyrene, p-methylstyrene, m-methylstyrene, o-methylstyrene, p-ethylstyrene, m-ethylstyrene, o-ethylstyrene, t-butylstyrene, chlorostyrene, hydroxystyrene, t-butoxystyrene, vinyltoluene, and vinylnaphthalene. From the viewpoint of polymerizability, styrene is preferred.
[0044] Examples of the acrylamide compound include (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and (meth)acryloylmorpholine, and (meth)acrylamide, N,N-dimethyl(meth)acrylamide, and N,N-diethyl(meth)acrylamide are preferred.
[0045] Examples of (meth)acrylic acid ester monomers excluding (meth)acrylic acid alkyl esters include phenyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, glyceryl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, and alkylene oxide adducts of (meth)acrylic acid. From the viewpoint of improving affinity to metal surfaces and hydrophilicity, preferred are 2-hydroxyethyl (meth)acrylate and glyceryl (meth)acrylate. In the case of a dispersant, the molar ratio of the monomer (C) is 0 to 98 mol %, but from the viewpoints of dispersibility and solvent solubility, it is preferably 10 to 70 mol %, and more preferably 50 to 70 mol %.
[0046] Among the monomers (C), a (meth)acrylic acid polyoxyalkylene ester represented by the following general formula (2) is preferred. [ka] (In formula (2), R 1 is a hydrogen atom or a methyl group, R 2 is a hydrogen atom or an alkyl group having 1 to 22 carbon atoms, OA is an oxyalkylene group having 2 to 4 carbon atoms; n is the average number of moles of the oxyalkylene group added and is 1 to 50.
[0047] The number of moles of the oxyalkylene group added in the (meth)acrylic acid polyoxyalkylene ester is 1 to 50, preferably 3 to 30 from the viewpoint of dispersibility and polymerizability, more preferably 5 to 20. The moiety represented by R2 is a hydrogen atom or an alkyl group having 1 to 22 carbon atoms, preferably a hydrogen atom or an alkyl group having 1 to 18 carbon atoms from the viewpoint of affinity to the solvent or the dispersed substance, more preferably a hydrogen atom or a methyl group, and particularly preferably a hydrogen atom. Examples of the oxyalkylene group include an oxyethylene group, an oxypropylene group, and an oxybutylene group, and from the viewpoint of controlling hydrophobicity and hydrophilicity, an oxyethylene group and an oxypropylene group are preferred. One or more of these oxyalkylene groups may be included, and when two or more types are included, they may have a random structure or a block structure.
[0048] (Monomer (C1)) The monomer (C1) having a carboxyl group is a monomer having one or more carboxyl groups in the molecule. The number of carboxyl groups in the monomer (C1) is more preferably one. Specific examples of the monomer (C1) include acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, citraconic acid, mesaconic acid, and itaconic acid, and acrylic acid and methacrylic acid are preferred in terms of copolymerization reactivity, solubility in an alkaline aqueous solution, and ease of availability. The monomer (C1) may be used alone or in combination of two or more kinds.
[0049] (Monomer (C2)) The other copolymerizable monomer (C2) is not particularly limited as long as it is a monomer that is copolymerizable with the monomers (A), (B), and (C1), and may contain one or more types. However, (meth)acrylic acid esters other than (meth)acrylic acid alkyl esters and aromatic vinyl compounds are preferred.
[0050] Examples of (meth)acrylic acid ester monomers other than (meth)acrylic acid alkyl esters include phenyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, glyceryl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, and ethylene oxide adducts of (meth)acrylic acid, among which benzyl (meth)acrylate is preferred. From the viewpoint of developability, 2-hydroxyethyl (meth)acrylate, glyceryl (meth)acrylate, and hydroxypropyl (meth)acrylate are preferred.
[0051] Examples of aromatic vinyl compounds include styrene, α-methylstyrene, p-methylstyrene, m-methylstyrene, o-methylstyrene, p-ethylstyrene, m-ethylstyrene, o-ethylstyrene, t-butylstyrene, chlorostyrene, hydroxystyrene, t-butoxystyrene, vinyltoluene, and vinylnaphthalene, with styrene being preferred.
[0052] [Molecular weight of copolymer] The weight-average molecular weight of the copolymer of the present invention can be determined in terms of polystyrene using gel permeation chromatography (GPC) and is preferably 10,000 to 500,000, more preferably 20,000 to 100,000. If the weight-average molecular weight of the copolymer is too low, the coating film becomes brittle and the rust prevention effect decreases, while if the weight-average molecular weight is too high, there is a risk of a decrease in solvent solubility or coatability due to increased viscosity.
[0053] [Molecular weight of copolymer constituting dispersant] The weight-average molecular weight of the copolymer constituting the dispersant of the present invention can be determined in terms of polystyrene using gel permeation chromatography (GPC), and is preferably 3,000 to 800,000, more preferably 5,000 to 50,000, and even more preferably 10,000 to 30,000. If the weight-average molecular weight of the copolymer is too low or too high, dispersibility may decrease.
[0054] [Molecular weight of resist resin] The weight-average molecular weight of the resist resin can be determined in terms of polystyrene using gel permeation chromatography (GPC) and is 3,000 to 100,000, preferably 4,000 to 50,000, and more preferably 5,000 to 30,000. If the weight-average molecular weight of the resist resin is too low, adhesion may be insufficient, and if the weight-average molecular weight is too high, resist properties such as developability may deteriorate.
[0055] (Ratio of monomers in resist resin) When the total amount of the monomers (A), (B), (C1), and (C2) constituting the polymer is taken as 100 mol %, the content of the monomer (A) is 1 to 40 mol %, preferably 3 to 30 mol %, more preferably 5 to 30 mol %, and particularly preferably 5 to 20 mol %.
[0056] When the total amount of the monomers (A), (B), (C1), and (C2) constituting the polymer is taken as 100 mol %, the content of the monomer (B) is 1 to 94 mol %, preferably 5 to 90 mol %, and more preferably 10 to 85 mol %. When the total amount of the monomers (A), (B), (C1) and (C2) constituting the polymer is taken as 100 mol %, the content of the monomer (C1) is 5 to 40 mol %, preferably 7 to 30 mol %, and more preferably 10 to 20 mol %.
[0057] When the total amount of the monomers (A), (B), (C1) and (C2) constituting the polymer is 100 mol %, the content of the other copolymerizable monomer (C2) is 0 to 93 mol %. By setting the content of the monomers (A) to (C2) within the above range, a resin film with good adhesion can be obtained even at room temperature and under high temperature and high humidity conditions.
[0058] [Method for producing monomer (A)] Monomer (A) of the present invention is a monomer having three adjacent hydroxy groups on the benzene ring. The monomer (A) can be obtained, for example, by addition reaction of a compound having three adjacent hydroxy groups and a carboxylic acid on a benzene ring with a compound having a (meth)acryloyl group and an epoxy group, and examples of the monomer (A) include monomers having the structure shown in the following formula (3).
[0059] [ka]
[0060] Examples of the compound having three adjacent hydroxyl groups and a carboxylic acid on the benzene ring include gallic acid and 2,3,4-trihydroxybenzoic acid, with gallic acid being preferred from the viewpoint of availability. Examples of the compound having a (meth)acryloyl group and an epoxy group include glycidyl (meth)acrylate, with glycidyl methacrylate being preferred from the viewpoint of ease of synthesis of the monomer (A).
[0061] The reaction can be carried out by mixing the two, raising the temperature as required, and using a known method. If necessary, a catalyst may be added. As for the reaction conditions, the temperature is preferably 50 to 150° C., more preferably 70 to 110° C. If the temperature is too low, the reaction may not proceed sufficiently, whereas if the temperature is too high, gelation may occur.
[0062] The addition reaction may be carried out using a catalyst, and known catalysts may be used as the catalyst, but tertiary amines, quaternary ammonium salts, organic phosphorus, organometallic catalysts, metal oxides, and metal hydroxides are preferred, and tertiary amines and quaternary ammonium salts are more preferred. Examples of the catalyst include tertiary amines such as triethylamine, tributylamine, and N,N-dimethylbutylamine, and quaternary ammonium salts such as tetrabutylammonium bromide, tetrabutylammonium chloride, trimethylbenzylammonium chloride, and triethylbenzylammonium chloride.
[0063] The amount of the catalyst used is preferably 0.01 to 30% by mass, more preferably 0.1 to 15% by mass, based on the compound having a phenolic hydroxyl group. If the amount of the catalyst used is small, the reaction may not proceed sufficiently, whereas if the amount of the catalyst used is large, coloring may occur.
[0064] In addition, during the reaction, a gas having a polymerization inhibitory effect may be introduced into the reaction system, or a polymerization inhibitor may be added. For example, the gas may be air, and the polymerization inhibitor may be hydroquinone, methoquinone, 2,6-di-t-butylphenol, etc. These inhibitors may be used alone or in combination of two or more. The amount of the inhibitor used is preferably 0.01 to 3 mass% relative to the compound having a (meth)acryloyl group and an epoxy group, and more preferably 0.04 to 1 mass%. When a gas having a polymerization inhibitory effect is introduced into the reaction system, it may be dehydrated with a desiccant such as silica gel. In addition, structural isomers are generated in this reaction, and they may be used after isolation or as a mixture of isomers.
[0065] The above reaction may be carried out in the presence of a solvent, for example, acetone, methyl ethyl ketone, ethyl acetate, butyl acetate, toluene, xylene, methanol, ethanol, tetrahydrofuran, dioxane, or the like. The monomer obtained by the above reaction may be used as it is, or may be purified by a known method such as crystallization or crystallization.
[0066] [Method for producing copolymer] Next, the method for producing the copolymer of the present invention will be described. The copolymer of the present invention can be obtained by radical polymerization of a mixture of a plurality of necessary monomers. The polymerization can be carried out by a known method. For example, solution polymerization, suspension polymerization, emulsion polymerization, etc. can be mentioned, but solution polymerization and suspension polymerization are preferred in terms of being easy to adjust the weight average molecular weight of the copolymer within the above range.
[0067] The polymerization initiator may be a known one. For example, di(4-t-butylcyclohexyl)peroxydicarbonate, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, and other organic peroxides, and 2,2'-azobisisobutyronitrile, and other azo-based polymerization initiators may be used. These polymerization initiators may be used alone or in combination of two or more. The amount of the polymerization initiator used can be appropriately set depending on the combination of monomers used, reaction conditions, and the like.
[0068] When the polymerization initiator is added, for example, the entire amount may be charged at once, or a part of the polymerization initiator may be charged at once and the rest may be added dropwise, or the entire amount may be added dropwise. It is preferable to add the polymerization initiator dropwise together with the monomers, since this makes it easier to control the reaction, and it is also preferable to add the polymerization initiator after the monomers are added dropwise, since this makes it possible to reduce the amount of residual monomers.
[0069] As the polymerization solvent used in the solution polymerization, one in which the monomer and the polymerization initiator are soluble can be used. Specific examples of the polymerization solvent include methanol, ethanol, 2-propanol, acetone, toluene, methyl ethyl ketone, and propylene glycol monomethyl ether.
[0070] The concentration of the monomers (total amount) relative to the polymerization solvent is preferably 10 to 70% by mass, more preferably 10 to 60% by mass, and particularly preferably 20 to 50% by mass. If the concentration of the monomer mixture is too low, the monomers tend to remain, which may result in a decrease in the molecular weight of the resulting copolymer, whereas if the monomer concentration is too high, it may become difficult to control heat generation. When the monomer is added, for example, the entire amount may be added at once, a part of the monomer may be added at once and the rest may be added dropwise, or the entire amount may be added dropwise. From the viewpoint of ease of controlling heat generation, it is preferable to add a part of the monomer at once and the rest may be added dropwise, or to add the entire amount dropwise.
[0071] The polymerization temperature depends on the type of polymerization solvent, and is, for example, 50° C. to 110° C. The polymerization time depends on the type of polymerization initiator and the polymerization temperature. For example, when di(4-t-butylcyclohexyl)peroxydicarbonate is used as the polymerization initiator, a polymerization time of about 6 hours is suitable when the polymerization temperature is set to 70° C.
[0072] By carrying out the above polymerization reaction, the copolymer according to the resin composition of the present invention is obtained. The obtained copolymer may be used as it is, or may be isolated by subjecting the reaction solution after the polymerization reaction to filtration or purification.
[0073] [Anti-rust coating composition] The copolymer of the present invention is particularly suitable as an anti-rust coating composition. In addition to the copolymer of the present invention, the anti-rust coating composition may contain a solvent and, if necessary, other components such as a rust inhibitor and an antioxidant.
[0074] Examples of the solvent include hydrocarbon solvents such as toluene and xylene, ester solvents such as ethyl acetate and butyl acetate, alcohol solvents such as methanol, ethanol, isopropyl alcohol, isobutyl alcohol, 1-butanol, and diacetone alcohol, ether solvents such as diethyl ether and tetrahydrofuran, glycol ether solvents such as ethylene glycol monobutyl ether, propylene glycol monomethyl ether, and propylene glycol monoethyl ether, glycol ether acetate solvents such as diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, and propylene glycol monomethyl ether acetate, terpineol solvents such as terpineol, dihydroterpineol, and dihydroterpineol acetate, and ketone solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone. These can be used alone or in combination of two or more.
[0075] The content of the copolymer in the anticorrosive coating composition is preferably from 5 to 80% by weight, more preferably from 10 to 50% by weight.
[0076] (Dispersion composition) The dispersion composition of the present invention contains a dispersant, a dispersion, and a solvent. Here, the total mass of the dispersant, dispersion and solvent is 100% by mass. In this case, the content of the dispersant is preferably 0.05 to 20% by mass. If the content of the dispersant is less than 0.05% by mass, sufficient initial dispersibility and dispersion stability may not be obtained, and even if the content exceeds 20% by mass, the effect commensurate with the content may not be obtained. From the viewpoint of initial dispersibility and dispersion stability, the content of the dispersant is preferably 0.1 to 15% by mass, more preferably 0.5 to 10% by mass.
[0077] The dispersion contained in the dispersion composition of the present invention may be an organic powder or an inorganic powder. Examples of the organic powder include organic pigments such as azo, diazo, condensed azo, thioindigo, indathrone, quinacridone, anthraquinone, benzimidazolone, phenylene, phthalocyanine, anthrapyridine, and dioxazine.
[0078] Examples of inorganic powders include metal powders such as iron, aluminum, chromium, nickel, cobalt, zinc, tungsten, indium, tin, palladium, zirconium, titanium, copper, silver, gold, and platinum; alloy powders consisting of two or more types of metals or a metal and a nonmetal; composite powders consisting of composite metal powders or alloy powders; and mixed powders consisting of two or more types of inorganic powders or an inorganic powder mixed with another powder.
[0079] Other examples of inorganic powders include powders of silicate minerals, other silicate compounds, carbonate compounds, sulfate compounds, hydroxide compounds, oxide compounds, nitride compounds, carbide compounds, titanate compounds, etc. Examples of inorganic powders include powders of kaolin, clay, talc, mica, bentonite, dolomite, calcium silicate, aluminum silicate, magnesium silicate, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, barium sulfate, aluminum sulfate, aluminum hydroxide, iron hydroxide, zirconium oxide, magnesium oxide, aluminum oxide, titanium oxide, iron oxide, zinc oxide, antimony trioxide, indium oxide, indium tin oxide, silicon carbide, tungsten carbide, aluminum nitride, silicon nitride, boron nitride, barium titanate, calcium titanate, strontium titanate, carbon black, glass fiber, carbon fiber, carbon nanofiber, and carbon nanotubes (single-wall nanotubes, double-wall nanotubes, and multi-wall nanotubes).
[0080] Preferred examples of the dispersion include powders of metals such as nickel, cobalt, palladium, copper, silver, gold, and platinum; powders of oxide compounds such as zirconium oxide, magnesium oxide, aluminum oxide, iron oxide, zinc oxide, and indium tin oxide; and powders of titanate compounds such as barium titanate, calcium titanate, and strontium titanate.
[0081] From the viewpoint of usefulness, the average particle size of the dispersion is preferably 0.01 to 1 μm, more preferably 0.01 to 0.7 μm, and particularly preferably 0.01 to 0.5 μm. The average particle size of the dispersion can be measured by an electron microscope method using a SEM (scanning electron microscope) or a TEM (transmission electron microscope) or a microtrack method (laser diffraction / scattering method).
[0082] When the total amount of the dispersant, dispersion and solvent is 100 mass%, the content of the dispersion in the dispersion composition is usually 10 to 90 mass%, preferably 30 to 85 mass%, and more preferably 55 to 80 mass%.
[0083] Examples of the solvent (organic solvent) that serves as a dispersion medium for dispersing the dispersion in the dispersion composition of the present invention include aromatic hydrocarbon solvents such as toluene and xylene, hydrocarbon solvents such as cyclohexane, ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, ester solvents such as ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, and γ-butyrolactone, glycol ether solvents such as ethylene glycol monoethyl ether, ethylene glycol monoisopropyl ether, ethylene glycol mono n-butyl ether, diethylene glycol monoethyl ether, diethylene glycol mono n-butyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono n-propyl ether, propylene glycol mono n-butyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol mono n-propyl ether, and dipropylene glycol mono n-butyl ether, and ethylene glycol mono ethyl ether solvents such as propylene glycol mono n-butyl ether. Examples of the solvent include glycol ether ester solvents such as ethanol, diethanolamine, isopropyl alcohol, isopropyl alcohol, and ethyl alcohol. Examples of the solvent include glycol ether ester solvents such as ethanol, diethanolamine ... The content of the solvent in the dispersion composition is usually 5 to 50% by mass, preferably 10 to 40% by mass, and more preferably 10 to 30% by mass.
[0084] The dispersion composition of the present invention may contain various additives such as other surfactants, binders, plasticizers, and antifoaming agents, within the scope of not impairing the object of the composition.
[0085] The dispersion composition of the present invention can be produced according to a known method for producing a dispersion composition, for example, a method in which a dispersion is added to a solvent in which the dispersion is dissolved, and then the mixture is stirred and mixed at room temperature, or a method in which a solvent and a dispersant are added to the dispersion, and then the mixture is stirred and mixed at room temperature, etc.
[0086] As a dispersing device for stirring, mixing, or dispersing, a known dispersing machine can be used. Examples of the dispersing machine include a roll mill, a ball mill, a bead mill, a sand mill, a homogenizer, a disperser, and a rotation-revolution type mixer. Dispersion treatment can also be performed in an ultrasonic bath.
[0087] [Resist resin composition] The resist resin of the present invention may be used as a resist resin composition comprising a photopolymerization initiator, a polymerizable compound, and a solvent. The photopolymerization initiator is a compound that becomes the starting point of the polymerization reaction of the polymerizable compound by light irradiation, and any known photopolymerization initiator can be used. The wavelength is not particularly limited, but an initiator type suitable for the wavelength can be selected and used. The photopolymerization initiator in the present invention can be used alone or in combination of two or more kinds.
[0088] Examples of the photopolymerization initiator of the present invention include aromatic ketones such as benzophenone, N,N'-tetraalkyl-4,4'-diaminobenzophenone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-propanone-1, 4,4'-bis(dimethylamino)benzophenone (Michler's ketone), 4,4'-bis(diethylamino)benzophenone, and 4-methoxy-4'-dimethylaminobenzophenone; quinones such as alkylanthraquinone and phenanthrenequinone; benzoin compounds such as benzoin and alkylbenzoin; benzoin ether compounds such as benzoin alkyl ether and benzoin phenyl ether; benzyl derivatives such as benzil dimethyl ketal; 2-(o-chlorophenyl)-4,5-diphenylimidazole dimer, 2-(o-chlorophenyl)-4,5-di(m-methoxy ... 2,4,5-triarylimidazole dimers such as 2-(o-fluorophenyl)-4,5-diphenylimidazole dimer, 2-(o-methoxyphenyl)-4,5-diphenylimidazole dimer, 2,4-di(p-methoxyphenyl)-5-phenylimidazole dimer, and 2-(2,4-dimethoxyphenyl)-4,5-diphenylimidazole dimer, N-phenylglycine, and N-phenylglycine derivatives. Examples of compounds that can be used include acridine derivatives such as 9-phenylacridine, oxime esters such as 1,2-octanedione, 1-[4-(phenylthio)-,2-(O-benzoyloxime)], coumarin compounds such as 7-diethylamino-4-methylcoumarin, thioxanthone compounds such as 2,4-diethylthioxanthone, and acylphosphine oxide compounds such as 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide. The content of the photopolymerization initiator is preferably 0.01% by mass to 50% by mass, more preferably 0.1% by mass to 40% by mass, and further preferably 0.1% by mass to 30% by mass, based on the total solid content of the photosensitive resin composition.
[0089] The polymerizable compound is a compound having at least one polymerizable functional group, and any known compound can be used. Examples of the polymerizable compound include 2-hydroxyethyl (meth)acrylate, carbitol (meth)acrylate, isobornyl (meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,6-hexane glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, )acrylate, glycerin di(meth)acrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc. are included, and compounds having two or more polymerizable functional groups are preferred, and two or more types may be used in combination.
[0090] The content of the polymerizable compound is preferably 3% by mass to 200% by mass, more preferably 5% by mass to 150% by mass, and further preferably 10% by mass to 100% by mass, based on the total solid content of the photosensitive resin composition.
[0091] As the solvent, any known solvent may be used, and two or more of them may be used in combination. Examples of the solvent include methyl alcohol, ethyl alcohol, ethyl acetate, butyl acetate, acetone, methyl ethyl ketone, N,N-dimethylformamide, tetrahydrofuran, benzene, toluene, methoxyethoxyethanol, ethoxyethoxyethanol, diethylene glycol ethyl methyl ether, propylene glycol monomethyl ether, 2-methoxyethyl acetate, and propylene glycol monomethyl ether acetate. Other components such as a leveling agent can be added to the resist resin composition as long as they do not impair the effects of the present invention. EXAMPLES
[0092] [Examples of copolymers and rust-preventive compositions] (Synthesis of Monomer) Ethanol (Kishida Chemical Co., Ltd.), 50.0 g of gallic acid monohydrate (Tokyo Chemical Industry Co., Ltd.), and 2.4 g of triethylamine were charged into a 1 L flask equipped with a stirrer, a thermometer, a condenser, and a dropping funnel, and 51.3 g of glycidyl methacrylate (product name: Blenmar GH (NOF Corp.)) was added dropwise from the dropping funnel over 30 minutes, and the reaction was carried out at 80°C for 10 hours. 100 g of butyl acetate (Kishida Chemical Co., Ltd.) was added to the reaction solution, which was then washed with a 0.1 M aqueous solution of sodium bicarbonate and saturated saline. The butyl acetate layer after washing was concentrated to obtain a monomer having the structure shown in the following formula (3).
[0093] [ka]
[0094] Example 1 In a 1L separable flask equipped with a stirrer, a thermometer, a condenser and a nitrogen inlet tube, 150g of isopropanol (Kishida Chemical Co., Ltd.), 11.0g of monomer (A), 4g of glycerin monomethacrylate (product name: Blenmar GLM (NOF Corp.)), and 85g of 2-ethylhexyl methacrylate (Tokyo Chemical Industry Co., Ltd.) were charged, and the flask was replaced with nitrogen to create a nitrogen atmosphere. Then, 0.5g of 2,2'-azobis(2,4-dimethylvaleronitrile) (product name: V-65 (Wako Pure Chemical Industries, Ltd.)) was added, the temperature was raised to 75°C, and the mixture was reacted for 3 hours to obtain an isopropanol solution of copolymer A. The solvent was then removed at 60°C under reduced pressure for 180 minutes to obtain the copolymer of Example 1.
[0095] Example 2 The copolymer of Example 2 was obtained in the same manner as in Example 1, except that the amounts of the monomer (A) used were changed to 13 g, glycerin monomethacrylate to 5 g, and ethylhexyl methacrylate to 82 g.
[0096] Example 3 The copolymer of Example 3 was obtained in the same manner as in Example 1, except that the amounts of the monomer (A) used were 30 g, glycerin monomethacrylate was 0 g, and ethylhexyl methacrylate was 70 g.
[0097] Example 4 The copolymer of Example 4 was obtained in the same manner as in Example 1, except that 13 g of monomer (A), 5 g of glycerin monomethacrylate, and 82 g of methyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) were used instead of ethylhexyl methacrylate.
[0098] Example 5 The copolymer of Example 5 was obtained in the same manner as in Example 1, except that the amount of 2,2'-azobis(2,4-dimethylvaleronitrile) used was changed from 0.5 g to 0.1 g.
[0099] Example 6 The copolymer of Example 6 was obtained in the same manner as in Example 1, except that the amounts of the monomer (A) and ethylhexyl methacrylate used were 5 g and 95 g, respectively.
[0100] (Polymerization Example 7) The copolymer of Example 7 was obtained in the same manner as in Example 1, except that the amount of monomer (A) used was 11 g, the amount of glycerin monomethacrylate used was 4 g, and styrene was used in place of ethylhexyl methacrylate at 85 g.
[0101] Comparative Example 1 The copolymer of Comparative Example 1 was obtained in the same manner as in Example 1, except that the amount of the monomer (A) used was 0 g and the amount of ethylhexyl methacrylate used was 100.0 g.
[0102] Comparative Example 2 The copolymer of Comparative Example 2 was obtained in the same manner as in Example 4, except that the amounts of the monomer (A) used were 0 g, ethylhexyl methacrylate was 90 g, and glycerin monomethacrylate was 10 g.
[0103] [Adhesion test] A glass substrate (26 mm × 76 mm) was washed with ethanol, hexane, and acetone, and various copolymer solutions dissolved in tetrahydrofuran (THF) were applied at 1.2 mg / cm 2 The coating was applied so that the coating was uniform and dried at room temperature for 12 hours. The test was performed using the cross-cut method (JIS-K5600-5-6 adhesion, 1 mm intervals). Evaluation criteria ◎: No peeling ○: Peeling of 4 squares or less ×: 5 or more squares peeled off
[0104] [Rust prevention test] The copolymer was dissolved on a steel substrate (SPCC-SD 1mm x 25mm x 100mm) at 0.8mg / cm 2 The sample pieces were then immersed in a 3.5% NaCl aqueous solution and visually inspected for rust and changes in the coating. Evaluation criteria ◎: No rust ○: Rust is less than 10% of the total surface area ×: Rust is present in 10% or more of the total area
[0105] [Smoothness test] The copolymer was dissolved on a steel substrate (SPCC-SD 1mm x 25mm x 100mm) at 0.8mg / cm 2 The coating was applied so that the thickness of the coating was 100 μm, and the coating was dried at room temperature for 12 hours to prepare a sample piece. The coating film thus prepared was visually observed, and the smoothness was evaluated based on the presence or absence of surface defects. Evaluation criteria ◎: No defects found ○: Slight defects ×: Clear defects are observed
[0106] [Table 1]
[0107] As shown in Table 1, Examples 1 to 7 were excellent in all of adhesion, rust prevention, and smoothness. On the other hand, in Comparative Example 1, the copolymer did not contain the monomer (A), but the adhesion and rust prevention were low, and in Comparative Example 2, the polymer did not contain the monomer (A), but the rust prevention and smoothness were low.
[0108] [Examples of Dispersion Compositions] (Synthesis of Monomer) Ethanol (Kishida Chemical Co., Ltd.), 50.0 g of gallic acid monohydrate (Tokyo Chemical Industry Co., Ltd.), and 2.4 g of triethylamine were charged into a 1 L flask equipped with a stirrer, a thermometer, a condenser, and a dropping funnel, and 51.3 g of glycidyl methacrylate (product name: Blenmar GH (NOF Corp.)) was added dropwise from the dropping funnel over 30 minutes, and the reaction was carried out at 80 ° C. for 10 hours. 100 g of butyl acetate (Kishida Chemical Co., Ltd.) was added to the reaction liquid, and the mixture was washed with 0.1 M aqueous sodium bicarbonate solution and saturated saline solution in that order. The butyl acetate layer after washing was concentrated to obtain a monomer mainly composed of the structure shown in the following formula (3). [ka]
[0109] (Polymerization example 1: Copolymer A) In a 1L separable flask equipped with a stirrer, a thermometer, a condenser and a nitrogen inlet tube, 400g of isopropanol (Kishida Chemical Co., Ltd.), 10.0g of monomer (A), 20.0g of butyl methacrylate (Tokyo Chemical Industry Co., Ltd.), and 70.0g of polypropylene glycol monomethacrylate (Blenmer PP-800, NOF Corp.) were charged, and the flask was replaced with nitrogen to create a nitrogen atmosphere. Then, 3.0g of 2,2'-azobis(2,4-dimethylvaleronitrile) (product name: V-65 (Wako Pure Chemical Industries, Ltd.)) was added, the temperature was raised to 75°C, and the reaction was carried out for 3 hours to obtain an isopropanol solution of copolymer A. Then, the solvent was removed at 60°C under reduced pressure for 180 minutes to obtain copolymer A.
[0110] (Polymerization example 2: Copolymer B) Copolymer B was obtained in the same manner as in Polymerization Example 1, except that the amount of 2,2'-azobis(2,4-dimethylvaleronitrile) used was changed from 3.0 g to 1.0 g.
[0111] (Polymerization example 3: Copolymer C) Copolymer C was obtained in the same manner as in Polymerization Example 1, except that the amount of the monomer (A) used was 20.0 g and the amount of the polypropylene glycol monomethacrylate used was 60.0 g.
[0112] (Polymerization example 4: Copolymer D) Copolymer D was obtained in the same manner as in Polymerization Example 1, except that the amount of the monomer (A) was 50.0 g and the amount of the polypropylene glycol monomethacrylate was 30.0 g.
[0113] (Polymerization example 5: Copolymer E) Copolymer E was obtained in the same manner as in Polymerization Example 1, except that methoxypolyethylene glycol monomethacrylate (BLEMMER PME-400, manufactured by NOF Corp.) was used instead of polypropylene glycol monomethacrylate.
[0114] (Polymerization example 6: Copolymer F) Copolymer F was obtained in the same manner as in Polymerization Example 1, except that stearyl methacrylate (Blenmer SMA, manufactured by NOF Corporation) was used instead of polypropylene glycol monomethacrylate.
[0115] (Polymerization example 7: Copolymer G) Copolymer G was obtained in the same manner as in Polymerization Example 1, except that the amounts of monomer (A) used were 0 g and 100.0 g of polypropylene glycol monomethacrylate were used.
[0116] (Polymerization example 8: Copolymer H) Copolymer H was obtained in the same manner as in Polymerization Example 1, except that the amount of Monomer (A) used was 0 g and the amount of methoxypolyethylene glycol monomethacrylate used was 100.0 g.
[0117] (Evaluation of Barium Titanate Dispersibility) 20.0 g of barium titanate powder (average particle size: 0.1 μm, measured by electron microscopy using SEM), 5.0 g of toluene / ethanol mixed solvent (3 / 7, mass ratio), and 0.4 g of dispersant were weighed into a 50 mL screw tube, and pre-dispersed by stirring for 5 minutes with a planetary centrifugal mixer. After that, the mixture was dispersed for 3 hours with 1.0 mm zirconia beads in a bead mill to obtain a slurry-like dispersion composition. For each dispersion composition, the shear viscosity was measured at a temperature of 25° C. and at shear rates of 0.1 to 100 (1 / s) using a dynamic viscoelasticity device (Paar Physica MCR-302, manufactured by Anton Paar). ◎: Viscosity at 3s-1 is 10 Pa s or less Good: Viscosity at 3s-1 is less than 500 Pa s ×: Viscosity at 3s-1 is 500 Pa s or more
[0118] (Nickel dispersion evaluation) 20.0 g of nickel powder (average particle size: 0.1 μm, measured by electron microscopy using SEM), 5.0 g of dihydroterpineol, and 0.2 g of dispersant were weighed into a 50 mL screw tube and stirred for 5 minutes with a planetary centrifugal mixer to obtain a slurry-like dispersion composition. For each dispersion composition, the shear viscosity was measured at a temperature of 25° C. and at shear rates of 0.1 to 100 (1 / s) using a dynamic viscoelasticity device (Paar Physica MCR-302, manufactured by Anton Paar). ◎: Viscosity at 3s-1 is 10 Pa s or less Good: Viscosity at 3s-1 is less than 50 Pa s ×: Viscosity at 3s-1 is 50 Pa s or more
[0119] [Paste Stability Evaluation] To 100 parts by weight of Ni powder (NFP201S, manufactured by JFE Minerals), 10 parts by weight of barium titanate, 1 part by weight of dispersant, 3 parts by weight of ethyl cellulose (STD100, manufactured by Dow), and 90 parts by weight of dihydroterpineol were added. The mixture was stirred using a planetary mixer, and then kneaded with a three-roll mill to obtain a Ni paste. The obtained paste was stored at 25°C, and the presence or absence of settling or separation of the paste was visually confirmed. ◎: No precipitation or separation of barium titanate was observed until the 28th. 〇: No sedimentation or separation of barium titanate observed after 7 days or more ×: Settling or separation of barium titanate observed within 7 days
[0120] [Table 2]
[0121] [Table 3]
[0122] [Table 4]
[0123] As shown in Tables 2 and 3, in Examples 11 to 16 of the present invention, the barium titanate dispersibility, nickel dispersibility, and paste stability were all good.
[0124] As shown in Table 4, the polymers of Comparative Examples 11 and 12, which did not contain the monomer (A), were all low in barium titanate dispersibility, nickel dispersibility and paste stability. In the polymer of Comparative Example 13, a polycarboxylic acid-based polymer was used, but both the nickel dispersibility and the paste stability were low. In the polymer of Comparative Example 14, a polyamine-based polymer was used, but both the dispersibility of barium titanate and the paste stability were low. In the polymer of Comparative Example 15, a polycarboxylic acid polymer and a polyamine polymer were used in combination, but both the nickel dispersibility and the paste stability were low.
[0125] [Examples of Resist Resin Composition] (Synthesis of Monomer A1) Ethanol (Kishida Chemical Co., Ltd.), 50.0 g of gallic acid monohydrate (Tokyo Chemical Industry Co., Ltd.), and 2.4 g of triethylamine were charged into a 1 L flask equipped with a stirrer, a thermometer, a condenser, and a dropping funnel, and 51.3 g of glycidyl methacrylate (product name: Blenmar GH (NOF Corp.)) was added dropwise from the dropping funnel over 30 minutes, and the reaction was carried out at 80 ° C. for 10 hours. 100 g of butyl acetate (Kishida Chemical Co., Ltd.) was added to the reaction liquid, and the mixture was washed successively with 0.1 M aqueous sodium bicarbonate solution and saturated saline. The butyl acetate layer after washing was concentrated to obtain a monomer A1 having the structure shown in the following formula (3).
[0126] [ka]
[0127] Example 21 A 1L separable flask equipped with a stirrer, a thermometer, a condenser, a dropping funnel and a nitrogen inlet tube was charged with 350g of propylene glycol monomethyl ether, and the flask was replaced with nitrogen to create a nitrogen atmosphere. A monomer solution was prepared by mixing 18.3g of Monomer A1, 7.6g of methacrylic acid ("MAA Monomer" manufactured by Kuraray Co., Ltd.), and 74.1g of cyclohexyl methacrylate ("Blenmer CHMA" manufactured by NOF Corporation), and a polymerization initiator solution was prepared by mixing 50g of propylene glycol monomethyl ether and 6.3g of 2,2'-azobis(2,4-dimethylvaleronitrile) (product name: V-65 (manufactured by Wako Pure Chemical Industries, Ltd.)).
[0128] The temperature inside the reaction vessel was raised to 75° C., and the monomer solution and the polymerization initiator solution were simultaneously dropped over 3 hours, respectively. After that, the reaction was carried out at 75° C. for 3 hours, and a propylene glycol monomethyl ether solution of the resist resin of Example 21 (resin solid content 20%) was obtained.
[0129] Example 22 A resist resin of Example 22 was obtained in the same manner as in Example 21, except that the monomer solution was changed to 26.7 g of Monomer A1, 12.3 g of acrylic acid ("Acrylic Acid" manufactured by Nippon Shokubai Co., Ltd.), 34.2 g of methyl methacrylate ("MMA Monomer" manufactured by Kuraray Co., Ltd.), and 26.6 g of styrene ("NS Styrene" manufactured by NS Styrene Monomer Co., Ltd.).
[0130] (Example 23) A resist resin of Example 23 was obtained in the same manner as in Example 21, except that the monomer solution was changed to 47.0 g of Monomer A1, 6.5 g of methacrylic acid, and 46.5 g of cyclohexyl methacrylate.
[0131] (Example 24) A resist resin of Example 24 was obtained in the same manner as in Example 21, except that the monomer solution was changed to 5.8 g of Monomer A1, 8.1 g of methacrylic acid, and 86.1 g of cyclohexyl methacrylate, and the amount of initiator in the polymerization initiator solution was changed to 3.0 g.
[0132] Comparative Example 21 A resist resin of Comparative Example 21 was obtained in the same manner as in Example 21, except that the monomer solution was changed to 5.8 g of acrylic acid, 40.2 g of methyl methacrylate, and 54.0 g of cyclohexyl methacrylate, and the amount of initiator in the polymerization initiator solution was changed to 3.0 g.
[0133] Comparative Example 22 A resist resin of Comparative Example 22 was obtained in the same manner as in Example 21, except that the monomer solution was changed to 12.9 g of methacrylic acid, 24.9 g of methyl methacrylate, and 62.2 g of styrene, and the amount of initiator in the polymerization initiator solution was changed to 3.0 g.
[0134] [Measurement of weight average molecular weight] The weight average molecular weight (Mw) was determined by gel permeation chromatography (GPC) under the following conditions. Equipment: Tosoh Corporation, HLC-8220 Column: Shodex, LF-804 Standard material: polystyrene Eluent: THF (tetrahydrofuran) Flow rate: 1.0ml / min Column temperature: 40℃ Detector: RI (Differential Refractive Index Detector)
[0135] [Evaluation of developability] The resist resin solution was spin-coated onto a silicon wafer and dried at 120°C to obtain a resin film with a thickness of 3 μm. This silicon wafer was immersed in a 1% aqueous sodium hydroxide solution for 30 seconds. After immersion, the silicon wafer was visually observed to evaluate whether or not the polymer remained. When no resist resin remained, it was marked as "○", and when the resist resin remained, it was marked as "×".
[0136] [Evaluation of Room Temperature Adhesion] The resist resin solution was applied to an alkaline glass plate using a bar coater and dried at 120°C for 5 minutes to obtain a resin film with a thickness of 5 μm. 100 squares were cut into the film, and Cellotape® (manufactured by Nichiban) was attached to the film. The Cellotape® was then peeled off, and the adhesion was evaluated based on the number of squares remaining and the appearance. Those with no peeled squares and no chipped corners were rated as "O", those with no peeled squares but some chipped corners were rated as "△", and those with some peeled squares were rated as "X". The number of peeled squares was also counted, and the evaluation was made by dividing the number of peeled squares by the total number of squares.
[0137] [Appearance after high temperature and humidity conditions] A diluted solution of 10g of resist resin solution mixed with 10g of propylene glycol monomethyl ether was applied to an alkaline glass using a bar coater, and dried at 120°C for 5 minutes to obtain a resin film with a thickness of 5 μm. This film was placed in a thermohygrostat (HASTEST PC-242HSR2 manufactured by Hirayama Seisakusho Co., Ltd.) set at a temperature of 100°C and a humidity of 100%, and left to stand for 2 hours. The appearance of the film after high temperature and high humidity treatment was evaluated visually.
[0138] [Adhesion after high temperature and humidity conditions] A diluted solution of 10g of resist resin solution mixed with 10g of propylene glycol monomethyl ether was applied to an alkaline glass using a bar coater, and dried at 120°C for 5 minutes to obtain a resin film with a thickness of 5 μm. This film was placed in a thermohygrostat (HASTEST PC-242HSR2 manufactured by Hirayama Seisakusho Co., Ltd.) set at a temperature of 100°C and a humidity of 100%, and left to stand for 3 hours. After high temperature and high humidity treatment, 100 squares were cut into the film, cellophane tape (manufactured by Nichiban) was attached, the cellophane tape was peeled off, and the adhesion was evaluated based on the number of squares and the appearance. Those with no peeled squares and no chipped corners were rated as "◎", those with no peeled squares but some with chipped corners were rated as "◯", and those with some peeled squares were rated as "X". The number of peeled squares was also counted, and the evaluation was performed by dividing the number of peeled squares by the total number of squares.
[0139] [Table 5] MMA: Methyl methacrylate CHMA: Cyclohexyl methacrylate AA: Acrylic acid MAA: Methacrylic acid St: Styrene
[0140] [Table 6] MMA: Methyl methacrylate CHMA: Cyclohexyl methacrylate AA: Acrylic acid MAA: Methacrylic acid St: Styrene
[0141] As shown in Table 5, the resist resin of the present invention can provide a resin film with good adhesion even under room temperature and high temperature and high humidity conditions.
[0142] As shown in Table 6, the resist resin of Comparative Example 21 did not use monomer (A), but the appearance and adhesion after high-temperature, high-humidity treatment were deteriorated. The resist resin of Comparative Example 22 did not use monomer (A), but the appearance and adhesion after high-temperature, high-humidity treatment were deteriorated.
Claims
[Claim 1] An anti-rust coating composition comprising a copolymer and an organic solvent, The copolymer is a copolymer in which the molar ratio of the monomer (A) represented by the following general formula (1) is 1 to 99 mol %, the molar ratio of the (meth)acrylic acid alkyl ester (B) having 1 to 22 carbon atoms is 1 to 99 mol %, the molar ratio of the other copolymerizable monomer (C) is 0 to 98 mol %, and the weight average molecular weight is 3,000 to 1,000,000. 【Chemistry 1】 (In formula (1), R is a hydrogen atom or a methyl group; X represents an alkylene group having 2 to 5 carbon atoms or an alkylene group having 2 to 5 carbon atoms and one hydroxyl group.
Citation Information
Patent Citations
Silver halide photographic sensitive material
JP1989198742A
Dental adhesive
JP1995138119A
Resist composition for color filter, and color filter
JP1998133370A
Tanning developing agent, silver halide photosensitive material, tanning developer and relief image forming method
JP2001215732A
Positive resist composition and method for forming pattern by using the same
JP2006091662A